2011
DOI: 10.1371/journal.pone.0021139
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Hormone Regulates Extreme Mandible Growth in Male Stag Beetles

Abstract: The morphological diversity of insects is one of the most striking phenomena in biology. Evolutionary modifications to the relative sizes of body parts, including the evolution of traits with exaggerated proportions, are responsible for a vast range of body forms. Remarkable examples of an insect trait with exaggerated proportions are the mandibular weapons of stag beetles. Male stag beetles possess extremely enlarged mandibles which they use in combat with rival males over females. As with other sexually sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 107 publications
(119 citation statements)
references
References 24 publications
5
114
0
Order By: Relevance
“…These include caste determination in social insects [35], photoperiodic adaptation of reproductive modes in aphids [36], seasonal pattern formation in butterflies [37], as well as the development of colour in caterpillars [38], horns in scarab beetles [39,40] and morphological defences in Daphnia [11,16]. All of these are mediated by juvenile hormones and often dopamine-signalling pathways [41][42][43][44], as supported by the data presented here.…”
Section: Signalling Pathway Of Environmentally Induced Polyphenismssupporting
confidence: 63%
“…These include caste determination in social insects [35], photoperiodic adaptation of reproductive modes in aphids [36], seasonal pattern formation in butterflies [37], as well as the development of colour in caterpillars [38], horns in scarab beetles [39,40] and morphological defences in Daphnia [11,16]. All of these are mediated by juvenile hormones and often dopamine-signalling pathways [41][42][43][44], as supported by the data presented here.…”
Section: Signalling Pathway Of Environmentally Induced Polyphenismssupporting
confidence: 63%
“…We previously reported that JH promotes mandible enlargement, and that larger males have higher JH titers than smaller males during the prepupal period (Gotoh et al 2011). The effects of dac knockdown on mandible size exhibited a significant interaction with body size (Fig.…”
Section: Potential Interaction Of Patterning Genes With Jh Signaling mentioning
confidence: 71%
“…Methods for rearing, breeding and inducing large and small males are described in Gotoh et al 2011 andGotoh et al 2014.…”
Section: Insect Husbandrymentioning
confidence: 99%
See 2 more Smart Citations